2012
DOI: 10.1016/j.stem.2012.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Derivation of Purified Lung and Thyroid Progenitors from Embryonic Stem Cells

Abstract: SUMMARY Two populations of Nkx2-1+ progenitors in the developing foregut endoderm give rise to the entire post-natal lung and thyroid epithelium, but little is known about these cells, as they are difficult to isolate in a pure form. We demonstrate here the purification and directed differentiation of primordial lung and thyroid progenitors derived from mouse embryonic stem cells (ESCs). Inhibition of TGFβ and BMP signaling, followed by combinatorial stimulation of BMP and FGF signaling can specify these cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
467
4
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 360 publications
(491 citation statements)
references
References 58 publications
15
467
4
1
Order By: Relevance
“…We describe the differentiation of human iPSCs to a functional epithelium containing multiciliated, Clara, goblet, and basal cells in a polarized layer with functional CFTR activity analogous to that observed with mouse iPSCs (32,55). Multiciliated cells (MCCs) are a very specialized cell type in which hundreds of centrioles are generated in postmitotic progenitor cells.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…We describe the differentiation of human iPSCs to a functional epithelium containing multiciliated, Clara, goblet, and basal cells in a polarized layer with functional CFTR activity analogous to that observed with mouse iPSCs (32,55). Multiciliated cells (MCCs) are a very specialized cell type in which hundreds of centrioles are generated in postmitotic progenitor cells.…”
Section: Discussionmentioning
confidence: 95%
“…S9A). It is worth noting that currently available in vitro differentiation lung progenitor differentiation protocols have also observed contamination of the lung endoderm differentiation with thyroid, neuronal, and mesodermal differentiation (31,32).…”
Section: Resultsmentioning
confidence: 99%
“…These progenitors could then be induced to respiratory differentiation, as evident from the expression of a wide variety of respiratory epithelial markers after further differentiation in FGF2 and FGF10. Future studies will work on the later differentiation events in fetal lung development to identify the signals regulating the development and contribution of the primordial lung progenitors to continued respiratory development (35).…”
Section: Session 2: Embryonic Stem Cells Ipscs and Lung Regenerationmentioning
confidence: 99%
“…Recently, elegant studies demonstrated self-formation of two ectoderm-derived complex organs, adenohypophysis 13 and optic cup 12 , using threedimensional mESC culture systems, as well as the capacity of colon stem cells to recapitulate in vitro the self-organization of an endoderm-derived tissue, the crypt-villus structures 22,23 . Although a few previous studies reported on the detection of thyrocyte-like cells in ESC cultures [24][25][26][27] , the present study is the first to demonstrate self-formation of thyroid follicles from mESC-derived TFC and their capacity for iodide organification in vitro. Importantly, when transplanted into mice, the mESC-derived cells generated functional thyroid tissue able to rescue thyroid hormone deficits in athyreoid animals.…”
Section: Discussionmentioning
confidence: 56%